The impact of external environment factors on the growth of cultural enterprises in China. (1st November 2016) - Lin, Wenhe; Hu, Yichung; Jiang, Peng
Abstract: Based on the summary and comments of enterprises growth theories, Delphi method was used to select external environment factors affecting the growth of cultural enterprises, and ANP method was used to calculate the relative weights of criteria and index to acquire the significant order. The conclusion showed the high degree of importance to the end that are, government support, financial ecological environment, development of cultural and creative industries, cultural resources situation, regional innovation network, and development of related supporting industries.